Implementing Innovative Credit Scoring (ICS) for Credit Risk Assessment and Loan Origination - Supriadi, Iman; Maghfiroh, Rahma Ulfa; Abadi, Rukhul (Otoritas Jasa Keuangan, 2025)
This research aims to analyze the implementation of Innovative Credit Scoring (ICS) in the financial industry through case studies of banks and fintech startups. This research uses a qualitative approach with case studies as the primary research design. The results show that ICS can improve process efficiency, scoring accuracy, and inclusiveness of credit access. ICS has significant practical implications, including improved efficiency, more accurate risk assessment, and more inclusive access to credit. Recommendations include cooperation with technology companies, regulatory oversight, attention to ethical aspects and algorithm bias, and developing a validation framework.